TINJAUAN KHES TERHADAP PEMANFAATAN TANAH GADAI DI DESA KADUR KABUPATEN PAMEKASAN - Atiqurrahman, Mohammad (IDEALITA: Jurnal Pendidikan dan Sosial Keagamaan, 2021)
The pawn agreement is a solution that is usually taken by the community when they get unexpected difficulties in funding. The implementation of the contract is when the pawnbroker (rahin) borrows a funds from the recipient of the pawn (murtahin), then rahin give a collateral, one of the them is land. The land is fully utilized by the murtahin without involving the rahin. This research was conducted in the village of Kadur, Kadur District, Pamekasan Regency, while the objectives of this study, are; The first, to find out the practice of land pawn agreements in the village of Kadur, Kadur District, Pamekasan Regency; The second, to find out the review of the Economic Syaria Law Compilation on the practice of land pawn contracts used by the people of Kadur Village, Kadur District, Pamekasan Regency. The research method used is qualitative research with the type of case study (field research). The results of the research are; The First, the land pawn agreement practiced by the People is based on a help each other, the process is that rahin visits the murtahin with the intention of borrowing money and giving the land as collateral (marhun), the delivery is based on truest each other. The period of time to redeem land that gived by marhun is at least two years. After the land is received by the murtahin, the land will be fully utilized by using it, and the results will be taken by themselves. The Second, according to the Economic Syariah Law Compilation, the practice of land pawning contracts that used by the people is in accordance with the pillars and conditions of pawning as stated in section 373-376. Beside it, the use of the pawned land by the murtahin is allowed, because in accordance with section 396, namely the murtahin may use it, if the rahin gives him permission to use the land that is collateraled, and the rahin has indicated this when the pawn contract is implemented even though it is not directly said, because it has been become a habit in society.Keywords: Economic Syariah Law; Utilization of Pawn Land